Implementasi Algoritma K-Means pada Kesiapan Guru Menyelenggarakan Pembelajaran Daring - Eka Budhi Santosa (Jurnal Pendidikan Edutama, 2022)
Abstract: Teachers need certain characteristics to be ready to organize online learning. The purpose of this research is to see the readiness of teachers in conducting online learning. The characteristics of the teachers collected were gender, generational, last education, teacher tenure, teacher's internet self-efficacy level, learning environment and variations of online learning models. This study uses the K-Means algorithm for clustering, then the analysis of the relationship between variables is used by Spearman's rho. The K-Means algorithm was performed on a dataset of 285 teachers. The results of the K-Means analysis obtained 8 clusters with various characteristics of each cluster. Furthermore, the Spearmans Rho Correlation analysis obtained significant correlation results with probability values > 0.05 being "Generation" and "Teacher tenure" as well as "Environment" and "Variation of online learning models". The relationship between “Generation” and “Teacher tenure” is positive and moderate. Meanwhile, the relationship between "Environment" and "Variation of online learning models" is positive and moderate. That is, the better the learning environment, the teachers tend to use more varied online learning models.Keyword: K-Means, Teacher characteristics, Online learning  Abstrak: Guru membutuhkan karakteristik tertentu supaya siap menyelenggarakan pembelajaran daring. Tujuan penelitian ini adalah melihat kesiapan guru dalam menyelenggarakan pembelajaran daring. Karakteristik guru yang dikumpulkan adalah gender, kelompok generasi, pendidikan terakhir, masa kerja guru, tingkat internet self efficacy guru, lingkungan pembelajaran dan variasi model pembelajaran daring. Penelitian ini menggunakan algoritma K-Means untuk clustering, selanjutnya analisis hubungan antar variabel digunakan Spearman’s rho.  Algoritma K-Means dilakukan pada dataset 285 guru. Hasil analisis K-Means didapatkan 8 cluster dengan karakteristik tiap klaster yang beragam. Selanjjutnya analisis Korelasi Spearmans Rho diperoleh hasil korelasi yang signifikan dengan nilai probabilitas >0,05 adalah “Generasi” dan “Masa kerja guru” serta “Lingkungan” dan “Variasi model pembelajaran daring”. Hubungan antara “Generasi”  dan “Masa kerja guru” bersifat positif dan sedang. Sedangkan, hubungan antara “Lingkungan”  dan “Variasi model pembelajaran daring” bersifat positif dan sedang. Artinya, semakin baik lingkungan pembelajaran maka guru cenderung akan menggunakan model pembelajaran daring lebih variatif.Kata kunci: K-Means, karakteristik guru, pembelajaran daring